Inflammatory Conditions of the Hip - Schueller-Weidekamm, Claudia; Teh, James (Seminars in Musculoskeletal Radiology, 2017)
Most cases of adult hip pain are related to osteoarthritis, so inflammatory causes are often not considered. This review article describes the different entities of hip inflammation and provides an approach on how to differentiate rheumatologic disorders from degenerative changes, synovial tumors, and infection. Indications for imaging, the correct choice of imaging modality, and scanning protocols are also discussed. The differential diagnosis of inflammatory lesions of the hips is addressed in the context of image interpretation.
Keywords: hip joint; magnetic resonance imaging; inflammation; diagnosis